If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2xh) + (2xh) + (h + h) = 180 Combine like terms: h + h = 2h (2hx) + (2hx) + (2h) = 180 (2hx) + (2hx) + (2h) = 180 Reorder the terms: (2h) + (2hx) + (2hx) = 180 Combine like terms: (2hx) + (2hx) = 4hx (2h) + 4hx = 180 Solving (2h) + 4hx = 180 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Reorder the terms: -180 + (2h) + 4hx = 180 + -180 Combine like terms: 180 + -180 = 0 -180 + (2h) + 4hx = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(-90 + h + 2hx) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-90 + h + 2hx)' equal to zero and attempt to solve: Simplifying -90 + h + 2hx = 0 Solving -90 + h + 2hx = 0 Move all terms containing h to the left, all other terms to the right. Add '90' to each side of the equation. -90 + h + 90 + 2hx = 0 + 90 Reorder the terms: -90 + 90 + h + 2hx = 0 + 90 Combine like terms: -90 + 90 = 0 0 + h + 2hx = 0 + 90 h + 2hx = 0 + 90 Combine like terms: 0 + 90 = 90 h + 2hx = 90 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 16x+9=15x-4 | | (X+7)(3x+5)=0 | | 3(4x-3.2)=5x-9.6 | | 3(2-3x)=52 | | 2x-4+3x=7x-3 | | 70x+90=90 | | 7x-5=5x-6 | | x^2-6x=22 | | 6u-9+3(2u+3)=4(u+3) | | 4(x+1.78)=3x | | 8n+16=8 | | 200x-0.08=600x+0.52 | | 3x+7=-2x+27 | | 6-6x=6x-10x+10 | | 3.9x-73=2.4x+5 | | 8z-24=6+2z | | 5m-7=10+3m | | 6.2=8x+1.4 | | 6-6x=6x-10+10 | | 6n-2=1 | | -4(v-4)=-7+37 | | 2y-8+14=-6 | | 2t-7=-16+t | | 3+3u=6 | | -19=5(u-5)-8u | | -3x^3+3x^2-21x+7=0 | | p-24=-19 | | 4+x-6=6x+3x+2 | | 4x-13.2=x | | 2.4x-8.6=10.6 | | -5+2u=-13 | | 17+7=31 |